Allelic Variants Interaction of CLOCK Gene and G-Protein β3 Subunit Gene with Diurnal Preference - Lee, Heon-Jeong; Paik, Jong-Woo; Kang, Seung-Gul; Lim, Se-Won; Kim, Leen (Chronobiology international, 2007)
The 3111 C T single nucleotide polymorphism (SNP) in the CLOCK gene and the 825C T SNP in the G-protein β3 subunit gene (GNB3) have been reported to influence diurnal preference. This study has attempted to characterize the association between the CLOCK gene and GNB3 polymorphisms and diurnal preference in healthy Korean college students. All subjects completed the 13-item Composite Scale for Morningness (CSM). The interaction between the 3111 C T SNP in the CLOCK gene and the 825 C T SNP in the GNB3 gene significantly influenced diurnal preference, according to the CSM Performance subscore (F=10.94, p=0.001). However, when the different polymorphisms of the two genes were analyzed independently, no direct correlations with diurnal preference were detected. The CLOCK gene 3111 C T SNP and GNB3 gene 825 C T SNP were found to manifest a gene-gene interaction that affects diurnal preference.